?REAGENTS FOR NEW HETEROANNELATION REACTIONS: AZA REAGENTS (Biological Sciences - PJSIR, 2000)
Aza reagents were prepared from different hydrazides. Reactions of ortho-aminoesters and ortho-aminonitriles with aza reagents have been studied in different solvents. Aza reagents with ortho-aminoesters and ortho-aminonitriles in presence ofp-toluene sulphonic acid in dry CHJCN or acetic acid furnished the tricyclic derivatives N~[2-(methylthio)-4-oxo-5, 6, 7, 8-tetrahydro [I]benzothieno [2, 3-d]pyrimidine-3 (4H)-yl]carbamic acid ethyl ester (8), 5, 6, 7, 8-tetrahydro-2-methylthio- 4-oxo [I] benzothieno [2, 3-d]pyrimidin-3 (4H) acetamide (9) and 5, 6, 7, 8-tetrahydro-2-methylthio-4-oxo [I] benzothieno [2, 3-d]pyrimidine-3 (4H)-benzamide (10), whereas, in pyridine medium these reactions afforded uncyclized urethane products (11, 12 and 13). .